Economic Policy Uncertainty in Turkey - Jirasavetakul, La-Bhus Fah (IMF Working Papers; Working Paper ;, 2018)
Uncertainty over economic policy plays a key role in economic outcomes. But evidence and quantification for emerging markets are elusive because of measurement and reverse causality issues. In this paper, we construct a news-based economic policy uncertainty (EPU) index for Turkey and assess how it affects Turkish firms. To disentangle the issues of endogeneity and reverse causality, we use a difference-in-differences approach, exploiting the fact that firms with a high share of irreversible investment are more exposed to policy uncertainty. In sectors with large irreversible investment EPU has a greater effect on growth, investment, and leverage. The results are robust to different definitions of investment irreversibility, lag structure, and selection of sectors.